Marketing Strategy in Increasing Occupancy Rate at The Jayakarta Lombok Beach Resort & Spa - Sudiarta, Made; Ramadhanty, Annisa (Language Assistance, 2024)
The purpose of this study is to explore effective marketing strategies for increasing the occupancy rate at The Jayakarta Lombok Beach Resort & Spa, emphasizing innovative approaches to attract and retain guests. A qualitative research method was employed, involving in-depth interviews with key stakeholders, analysis of promotional activities, and a review of occupancy trends over the past three years. Findings reveal that leveraging digital marketing, optimizing pricing strategies, and enhancing customer loyalty programs significantly contribute to higher occupancy rates. The originality of this study lies in its focus on the resort’s localized marketing initiatives and their alignment with emerging tourism trends in Lombok. However, the study is limited by its scope, which focuses on a single resort, suggesting the need for broader comparative research across similar properties. Practical implications include actionable recommendations for resorts to integrate digital platforms and community-based tourism partnerships into their marketing efforts. Academically, this research highlights the importance of adaptive marketing strategies in dynamic tourism markets, offering a foundation for further studies on sustainable marketing in hospitality